Using Web-Based Questionnaires for Collecting Data on Risk Factors of Preterm Birth in Tripoli hospitals, Libya - Mohamed Abuagela; Abdurraouf Said (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Preterm birth is a leading cause of perinatal mortality and long-term morbidity as well as the long-term health consequences and cognitive outcomes. This study aimed to evaluate the risk factors and consequences of preterm birth. Methods. A prospective ross sectional study was conducted from July 2021 to October 2021, By using an E-Questionnaire (Web-based questionnaire). Participants have access to the Web-based questionnaire through a website link created specifically for the nationwide study. Results. A total of 101 cases from Tripoli University Hospital and Tripoli Central Hospital included in this study. Most of the preterm births were observed in the age group between 21 - 30 years old and their weights ranged between 60kg - 79kg. The current study showed stress at 64% (p= 0.003), working/standing for a long time at 61% (p= 0.021), and exposure to pollutants at 94% (p= 0.000) to be the most significant risk factor in preterm birth. Other factors such as: social support at 54% (p= 0.489) and uterine contractions at 58.4% (p = 0.091). Conclusion. Based on results, the study suggests prompt identification of all risk factors associated with preterm birth to apply immediate and appropriate specific interventions. Data from these studies provide a foundation and direction for future research in the area of racial disparity and indicated that some factors may not cause preterm birth.